The Sentence as a Functional Genre of Administrative Communication - Kowalczyk, Joanna (Respectus Philologicus, 2017)
This article analyses the function of a sentence as a representative genre of administrative discourse, which has the ability to form and transform legally relevant facts. Functional and pragmatic nature of the sentence, as a document, lies in the ability to mandatory oblige all recipients of the discourse. The aim of the article is to identify the main features and descriptions of the sentence as an administrative discourse genre, which in essence is the main way of interpretation, evaluation and qualification of social behaviour. The study analysis includes the sentence analysis, taking into account three criteria: ontological, causal and pragmatic. This publication also provides a method of qualification of legally relevant facts and the examples of its verbalisation. It is shown that under formal communications, the studied genre of the text is the main instrument of the imperative regulation of social relations. The author indicates that the sentence is a subjective and prescriptive type of administrative document. The sentence is a final explicit act. Fundamental pragmatics of the sentence is focused on identifying and revealing the will of the authorities and influencing the participants of discourse.
Keywords: sentence; judicial act; administrative discourse; official and legal communication